Poly(ethylene glycol) modified Mn2+ complexes as contrast agents with a prolonged observation window in rat MRA. Issue 86 (28th November 2017) - Wu, Changqiang; Yang, Li; Chen, Zhuzhong; Zhang, Houbing; Li, Danyang; Lin, Bingbing; Zhu, Jiang; Ai, Hua; Zhang, Xiaoming
Abstract : PEGylated Mn 2+ complexes show higher relaxivity and longer blood circulation time than free Mn 2+ complexes. Abstract : A novel rigid Mn 2+ complex (MnL) with pyridine and pyrrolidine rings was designed and synthesized. The complex was further modified with alkyne, and conjugated to azide-terminated PEG by click chemistry. PEGylated MnL shows considerably higher relaxivity (MnL-PEG2k-MnL: r 1 = 6.38 mmol −1 s −1 ; MnL-PEG4.6k-MnL: r 1 = 5.63 mmol −1 s −1 ) and much longer blood circulation time than free Mn 2+ complexes (MnL: r 1 = 3.73 mmol −1 s −1 ), providing a prolonged time window to acquire longitudinal images for rat contrast enhanced magnetic resonance angiography.